AVIATION IN INDIA: A HISTORICAL OVERVIEW - Hasnu, Santosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The history of commercial aviation transport in India started under British rule in the late 1920s. Soon an Indian entrepreneur J.R.D. Tata ventured into commercial aviation to promote Tata Airlines in 1932. In the inter-war period between World War I and World War II, the British Imperial Government viewed air transport as a strategic asset and enterprising promoters (both Europeans and Indians) saw an opportunity for profitable investment. The interests of imperial state and finance capital converged in the emergence of air transport in Asia as elsewhere. After India’s independence from colonial rule in 1947, there was a shift in government policy toward economic protectionism to shield Indian aviation industry from foreign competitions. Republican India nationalized the aviation industry in 1953. In so doing, this study adds to the existing scholarship related to the business history of South Asia and transport history.